Single‐cell transcriptome analysis reveals thyrocyte diversity in the zebrafish thyroid gland. (3rd November 2020) - Gillotay, Pierre; Shankar, Meghna; Haerlingen, Benoit; Sema Elif, Eski; Pozo‐Morales, Macarena; Garteizgogeascoa, Inés; Reinhardt, Susanne; Kränkel, Annekathrin; Bläsche, Juliane; Petzold, Andreas; Ninov, Nikolay; Kesavan, Gokul; et al.
Abstract: The thyroid gland regulates growth and metabolism via production of thyroid hormone in follicles composed of thyrocytes. So far, thyrocytes have been assumed to be a homogenous population. To uncover heterogeneity in the thyrocyte population and molecularly characterize the non‐thyrocyte cells surrounding the follicle, we developed a single‐cell transcriptome atlas of the region containing the zebrafish thyroid gland. The 6249‐cell atlas includes profiles of thyrocytes, blood vessels, lymphatic vessels, immune cells, and fibroblasts. Further, the thyrocytes show expression heterogeneity, including bimodal expression of the transcription factor pax2a . To validate thyrocyte heterogeneity, we generated a CRISPR/Cas9‐based pax2a knock‐in line that monitors pax2a expression in the thyrocytes. A population of pax2a ‐low mature thyrocytes interspersed in individual follicles can be distinguished. We corroborate heterogeneity within the thyrocyte population using RNA sequencing of pax2a ‐high and pax2a ‐low thyrocytes, which demonstrates 20% differential expression in transcriptome between the two subpopulations. Our results identify and validate transcriptional differences within the presumed homogenous thyrocyte population. Synopsis: This study molecularly characterizes the zebrafish thyroid gland and surrounding structures at single‐cell resolution. It identifies the major cell‐types and potential cross‐talk and uncovers genetic heterogeneity in thyroid follicular cells. A single‐cell transcriptome atlas of the zebrafish thyroid gland and the surrounding tissue identifies diverse cell‐types, including immune cells, fibroblasts and blood & lymphatic vessels, present in the organ. An in silico connectome outlines the potential cross‐talk between the various cell‐types. The thyroid follicular cells display heterogeneity in the expression of multiple genes, including the transcription factor pax2a. A CRISPR/Cas9‐based knock‐in zebrafish line for pax2a corroborates the expression heterogeneity for pax2a in thyroid follicular cells in vivo . Abstract : This study molecularly characterizes the zebrafish thyroid gland and surrounding structures at single‐cell resolution. It identifies the major cell‐types and potential cross‐talk and uncovers genetic heterogeneity in thyroid follicular cells.